2023
DOI: 10.1001/jamanetworkopen.2022.54752
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Orally Administered Δ9-Tetrahydrocannabinol When Coadministered With Cannabidiol on Δ9-Tetrahydrocannabinol Pharmacokinetics and Pharmacodynamics in Healthy Adults: A Randomized Clinical Trial

Abstract: ImportanceControlled clinical laboratory studies have shown that cannabidiol (CBD) can sometimes attenuate or exacerbate the effects of Δ9-tetrahydrocannabinol (Δ9-THC). No studies have evaluated differences in pharmacokinetics (PK) of Δ9-THC and pharmacodynamics (PD) between orally administered cannabis extracts that vary with respect to Δ9-THC and CBD concentrations.ObjectiveTo compare the PK and PD of orally administered Δ9-THC-dominant and CBD-dominant cannabis extracts that contained the same Δ9-THC dose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 42 publications
(101 reference statements)
1
23
0
1
Order By: Relevance
“…Indeed, except for CYP1A2, our oral CBD PBPK model successfully predicted the magnitude of CBD‐CYP probe drug interactions. CBD increased the AUC 0‐t of Δ9‐THC and the active metabolite 11‐OH Δ9‐THC, resulting in enhanced pharmacological effects of Δ9‐THC 22 . After completing our Δ9‐THC PBPK model (in progress), the CBD and Δ9‐THC models can be applied to predict CBD‐Δ9‐THC interactions, as well as CYP‐ or UGT‐mediated CBD and/or Δ9‐THC interactions for different combinations of Δ9‐THC and CBD present in cannabis products.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, except for CYP1A2, our oral CBD PBPK model successfully predicted the magnitude of CBD‐CYP probe drug interactions. CBD increased the AUC 0‐t of Δ9‐THC and the active metabolite 11‐OH Δ9‐THC, resulting in enhanced pharmacological effects of Δ9‐THC 22 . After completing our Δ9‐THC PBPK model (in progress), the CBD and Δ9‐THC models can be applied to predict CBD‐Δ9‐THC interactions, as well as CYP‐ or UGT‐mediated CBD and/or Δ9‐THC interactions for different combinations of Δ9‐THC and CBD present in cannabis products.…”
Section: Discussionmentioning
confidence: 99%
“…The study was conducted in cannabis-experienced healthy participants who signed the Johns Hopkins Medicine Institutional Review Boardapproved informed consent document (see Zamarripa et al 22 for details of inclusion and exclusion criteria as well as the CONSORT checklist; Table S1). The study is registered with the Clini calTr ials.gov database (NCT04201197).…”
Section: In Vivo Pharmacokinetic Interaction Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Lo anterior presume un uso recreacional de variedades fitomejoradas ricas en CBD lo cual podría ser un indicio de cambio en las dinámicas de consumo dentro de la ciudad, que favorecen los cuadros tóxicologicos cuando solo se consume cannabis con altos contenidos de THC sin CBD. El CBD al no poseer actividad psicotrópica tiene efectos neuroprotectores, antiinflamatorios y ansiolíticos, de igual manera existen estudios que indican que podría atenuar algunos de los efectos neurocognitivos y conductuales del THC (44,45,46) ; y aunque la evidencia de interacción entre ambos componentes no es concluyente por la existencia de estudios contradictorios (47,48) , la presencia de CBD en cannabis de uso recreativo se perfila como un posible factor a controlar, con el propósito de reducir los riesgos toxicológicos asociados al consumo (41,49) . Siguiendo esta línea, se observa que, en ensayos clínicos realizados para personas consumidoras de cannabis, las farmacoterapias basadas en CBD (cannabis con 0,4% de THC y 9% de CBD) han reducido la frecuencia de consumo de cannabis, las ansias y los síntomas de abstinencia (50) .…”
Section: Discussionunclassified
“…It has been reported that CBD can either attenuate or increase the effects of THC and that a pharmacokinetic interaction may occur through cytochrome P450 inhibition. Findings from a recent randomised clinical trial (RCT) with 18 healthy adults, in which the effects of oral 20 mg THC plus oral 640 mg CBD were compared to 20 mg THC alone and placebo, suggest that high doses of CBD can inhibit the metabolism of THC, resulting in stronger drug effects (greater impairment of cognitive and psychomotor activity, greater increase in heart rate) [ 78 ].…”
Section: Clinical Aspects Of Cannabis Productsmentioning
confidence: 99%